High-valent iron in biomimetic alkane oxidation catalysis - Grau,M; Britovsek,GJP (SPRINGER-VERLAG BERLIN, 2015)
The combination of iron salts or complexes with strong oxidants such as hydrogen peroxide results in the formation of high-valent iron oxo species, the nature of which has been under discussion in the chemical literature for more than a century. Recent advances in the design and development of molecular iron-based oxidation catalysts and their mechanistic understanding are summarised in this chapter, in particular iron complexes featuring tetradentate and pentadentate ligands. Inspired by enzymatic systems based on heme and nonheme ligand environments, the development of biomimetic iron-based catalysts for the selective oxidation of alkanes and alkenes can potentially be applied in a range of areas, from late stage functionalisation of natural product synthesis to large-scale oxidation of hydrocarbons.